Management of corpses during the COVID-19 pandemic in Spain() - González-Fernández, Jorge (Spanish Journal of Legal Medicine, 2020)
The Coronavirus/COVID-19 outbreak, declared a Public Health Emergency of International Importance on January 30, 2020 by the World Health Organization, has in many countries exceeded the capacity of health systems to respond, due to its high contagiousness and the capacity to manage the deceased, due to its high fatality risk. A review is necessary of the principal guidelines and protocols promoted by the institutions and the main scientific societies, aimed at containing the pandemic by adopting professional protection measures and appropriately managing the high number of cadavers. The temporary mortuaries in an epidemic crisis and the classification of bodies according to infectious risk are analysed. In particular the resolutions issued by the health authorities are summarised and the protocols for dealing with deaths during the COVID-19 pandemic are described, including forensic autopsies.